Cationic carbon monoxide-releasing polymers as antimicrobial and antibiofilm agents by the synergetic activity - Wang, Liping (2023)
Recent studies indicate that carbon monoxide-releasing molecules (CORMs), a class of organometallic compounds, exert antibacterial activities through the delivery of carbon monoxide (CO) molecules. We developed a new-class CO-delivery system by conjugating classical low-molecular-weight CORMs (i.e., [Ru(CO)3Cl2]2 and Mn(CO)5Br) onto a positively charged carrier, polyimidazolium (PIM), giving cationic CO-releasing polymers Ru@PIM and Mn@PIM, respectively. Compared with low-molecular-weight CORMs, our polymeric CO vehicles showed improved water solubility, reduced cytotoxicity, significantly extended CO-releasing duration, and enhanced antimicrobial ability against both planktonic and biofilm microorganisms. Ru@PIM and Mn@PIM inhibited the growth of a broad spectrum of free Gram-positive and Gram-negative bacteria as well as fungus with the lowest minimum inhibitory concentration (MIC) at 8 μg/mL. They were effective in preventing pathogenic Pseudomonas aeruginosa biofilm formation with biofilm reduction by more than 92% at 16 μg/mL and 99% at 32 μg/mL. They also demonstrated potent dispersal efficacy on recalcitrant well-established biofilms through a synergetic activity with a biofilm log10 reduction of 2.5-3.2 ≥ 64 μg/mL and nearly 2.0 at the concentration of as low as 16 μg/mL. This CO-releasing system may retain long-time antimicrobial ability after the complete release of CO molecules owing to the cationic structure. The novel CO-releasing polymers have great potential as antimicrobial and antibiofilm agents in biomedical applications.